TARAS SHEVCHENKO IN YEVHEN SVERSTYUK’S LITERARY PERCEPTION - Мафтин, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the spiritual foundations on which Yevhen Sverstyuk got developed as a personality and an artist. The role of T. Shevchenko’s image reception and his fate comprehension, the reception of Kobzar’s word in the publicist’s literary articles and essays were researched. The methodology of Ye. Sverstyuk as a Shevchenko scholar was analysed.